STRUKTUR DAN ESTETIKA ANGGUK PUTRI “SRI LESTARI” DI DUSUN PRIPIH KULON PROGO - Suryati, Suryati (Institut Seni Indonesia Yogyakarta, 2013)
The angguk is one among many types ofthe selawatan genre, it is an Indonesian traditional Islamic liturgical music. While the selawatan is normally perfomed by a group of men, the angguk includes a group of female dancers as the accompaniment to the selawatan musicians. This additional accompaniment accommodates the transformation form, from music to perfoming art. This study focuses on the analysis of structure and aesthetics of the performance ofthe “Sri Lestari” female angguk group in the Pripih village,at Kulon Progo district. The art was performed by young female dancers who were dressed in colorful costumesto attract the attention of audience. This study concludes that the performing art has been influenced by other type of the selawatan elements, such as the dolalak, which originated from Purworejo, Central Java. The angguk music which is very simple and monotous as the result of subsequent repetition with only little variations, is the verse reading effect of the pantun, which is a typical of traditional letter’s vocal arts. Whilethe pantun characterizes general musical structure, the instrumentation, rhythmic, and the tempo of the music, gives the essence of aesthetic meaning toward the genre. The dance has been used to enhance the performing aesthetics to invite the attention of the audience.Keywords: Angguk, selawatan, aesthetics.